MODELLING READING AWARENESS AND LEARNING HABIT THROUGH UNIVERSITY’S LIBRARY THEME BASED EXHIBITIONS (Practitioner Research, 2023)
From the perspectives of many, exhibitions are meant for museums and art galleries, but it can also be used as a tool for libraries to impart knowledge and learning process can be derived from displays of permanent collections or temporary exhibitions, the specimens or the interactive apparatus. The purpose of this study is to explore the perceptions of library users, who are students at a university, on organizing theme-based exhibitions around the setting in the library which would help to foster learning. This will boost the number of visitors to the libraries since the global digital revolution has affected both the traditional forms of disseminating knowledge and the frequency of visits to the library. The data for this study was collected from students of Universiti Utara Malaysia. A mixed method approach was employed consisting of a survey and focus group discussion. The study revealed two vital findings which are: (i) positive perception on the library as a place to impart knowledge, foster learning and on theme-based exhibitions as means to impart knowledge and foster learning and ii) the themes proposed are education, business and economics, technology, health care and wellness and lastly, trade and investment. The findings provide useful information for library management and ideas for improving the university’s library services. The findings also offer valuable insights for an integrated framework for developing theme-based exhibition design for libraries which could be an alternative form of communication between the library and its users.